Nurse and case manager views on improving access and use of healthcare for adults living in permanent supportive housing. Issue 2 (28th October 2021) - Schneiderman, Janet U.; Nedjat‐Haiem, Frances; Rivera, Dean; Pérez Jolles, Mónica
Abstract: Housing is one of the social determinants of health, and homelessness is associated with health inequalities including increased morbidity and decreased life expectancy. Services to improve access to and use of primary healthcare are provided to formerly homeless individuals (hereafter residents) who live in permanent supportive housing (PSH). Residents do not always utilize services, nor receive adequate healthcare, and often have poor health outcomes. The study aims were to explore nurse and case manager (hereafter participants) views on the challenges of providing healthcare to residents, and strategies to address challenges. This descriptive, qualitative study used thematic analysis. Five nurses and eight case managers working with residents of PSH agencies were interviewed using semistructured interviews. Five main themes emerged. The first theme of context of healthcare use included how the residents' history of homelessness, trauma, and survival affected using services. The second theme was how aspects of relationships (communication issues and mistrust) were barriers to care. The third theme was how residents' health issues (physical chronic diseases, mental health, and substance dependency) affected care. Community level barriers (insurance, financial hardship, and transportation) was the fourth theme. The final theme highlighted recommendations to improve access and use of healthcare by building rapport, addressing mistrust, and using effective communication techniques. Participants noted that barriers to healthcare use were often influenced by residents' previous homeless experience. Nurses noted that chronic physical health issues were problematic for residents. Participants expressed the need to take time to form an authentic relationship to increase trust with residents.